Spatially localized electrodeposition of multiple metals via light-activated electrochemistry for surface enhanced Raman spectroscopy applications. Issue 43 (24th April 2020) - Colombo, Rafael N. P.; Gonçales, Vinicius R.; Gautam, Shreedhar; Tilley, Richard; Gooding, J. Justin; Córdoba de Torresi, Susana I.
Abstract : Light is used to activate spatially and temporally resolved electrodeposition of multiple metals onto silicon. Abstract : Light can be used to address electrochemical reactions on a monolithic semiconducting electrode with spatial and temporal resolution. Herein, such principle was used for the electrodeposition of Au, Ag and Cu nanoparticles on a unique silicon-based electrode. The parallel nature of the process granted manufacturing speed and platforms were applied to discriminate molecules via multi-wavelength and multivariate Raman analysis.